Symptomatology following traumatic brain injury in a multidisciplinary clinic: experiences from a tertiary centre. (3rd September 2018) - Bell, Chris; Hackett, James; Hall, Benjamin; Pülhorn, Heinke; McMahon, Catherine; Bavikatte, Ganesh
Abstract: Background: Physical, cognitive and emotional sequelae in patients with traumatic brain injury (TBI) have been identified; some as late as two years post-injury. To aid in the specialist management of such patients, a multidisciplinary neurotrauma clinic was initiated at a tertiary centre.  Aim: This study sought to describe the clinical features of patients who attended the clinic. Methods: Patient data was collected under several categories: basic demographics, mechanism and severity of injury, initial CT findings and management, hospital stay and discharge details, symptoms in clinic and actions performed by clinic staff (medication changes, referrals to other services, etc.). Results: Three hundred and five patients met the inclusion criteria. Mean age was 47.5 and most patients were male (72.1%). Commonest mechanism of injury was falls (53.1%). 17.4% of injuries were classed as mild, 68.2% moderate and 14.1% severe. Commonest injury locations were frontal (21.6%) and temporal (16.1%) with contusions (37.4%) and subdural hematomas (27.9%) the commonest type of injury on initial CT scan. The most frequent physical complaints were headache (47.9%) and memory problems (42.0%). 7.9% complained of new seizures since TBI. 41.6% were referred to further services: most frequently psychology (19.3%) and neuropsychiatry (18.4%). Of 184 known to be employed before their injury, 48.4% of these returned to work before their last appointment. 28.5% were unable to continue driving. Conclusion: Our study provides an insight into the reality of long term sequelae of TBI, especially those at the more severe end of the spectrum, who are likely to present to tertiary or specialist services. Information gathered in this study about characteristics of the TBI population and their outcomes allows for better targeting of suitable patients for referral to a multidisciplinary clinic and improved resource planning.